Reading hotspots: a method to evaluate reader and mediator’s experience with children’s digital books - Menegazzi, Douglas; Sylla, Cristina (InfoDesign, 2023)
One of the main reasons why children’s reading is compromised in digital books are poorly designed hotspots – interaction areas. This study describes the development of a method to evaluate children’s and mediators’ experience while reading digital books on mobile interaction devices (MIDs). We reviewed and extended a set of metrics to assess the readers’ experience through ludic approaches and data-gathering methods. Building on previous research we extended the Multimodal Analysis model. The method was validated through empirical tests with 6 dyads of parent-child involved in joint reading in a total of 18 sessions. The results corroborate the effectiveness of the method informing the design and development of children’s books for MIDs.